2018
DOI: 10.1097/nnd.0000000000000419
|View full text |Cite
|
Sign up to set email alerts
|

Implementing a Process to Measure Return on Investment for Nursing Professional Development

Abstract: Return on investment (ROI) is one way to quantify the value that nursing professional development brings to the organization. This article describes a process to begin tracking ROI for nursing professional development. Implementing a process of tracking nursing professional development practitioners' ROI increased awareness of the financial impact and effectiveness of the department.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…There was an increase from baseline for yes responses to this question. When looking at organizational data to measure Level 4 evaluation outcomes, there are many confounding variables that can impact the results, making it difficult to ascertain if any improvements in organizational results can be attributed to an educational activity (Garrison & Beverage, 2018;J. D. Kirkpatrick & Kirkpatrick, 2016;Opperman et al, 2016;Pulliam Phillips, 2017).…”
Section: Wwwjnpdonlinecommentioning
confidence: 99%
See 1 more Smart Citation
“…There was an increase from baseline for yes responses to this question. When looking at organizational data to measure Level 4 evaluation outcomes, there are many confounding variables that can impact the results, making it difficult to ascertain if any improvements in organizational results can be attributed to an educational activity (Garrison & Beverage, 2018;J. D. Kirkpatrick & Kirkpatrick, 2016;Opperman et al, 2016;Pulliam Phillips, 2017).…”
Section: Wwwjnpdonlinecommentioning
confidence: 99%
“…Evaluation of continuing education activities can be a challenge for the NPD practitioner with multiple competing priorities, particularly for continuing education activities that require ongoing support for multilevel evaluation measures that occur after the activity has been completed (Baughman, 2019; Garrison & Beverage, 2018; Taylor & Hall, 2017). The robust evaluation strategy for this educational initiative required consideration of methods and resources to make this process efficient while generating data that would allow the NPD practitioner to determine the chain of impact from reaction to organizational results related to this educational initiative.…”
Section: Management Of the Evaluation Processmentioning
confidence: 99%
“…On the one hand, evidence added by empirical study, they have found increasing the baccalaureate nurses' (BSN) dose to 80% for every patient could potentially result in $5.6 million in savings annually that would more than offset annual costs of about $1.8 million in increased salaries associated with BSN qualifications. 19 On the other hand, management department tries to detect more efficient way to quantify the value that nursing professional development brings to the organization 20 and explored more undiscovered resource to assist nurses. For example, they found providing training curricula to non-nursing staff to provide feeding assistance for nutritionally at-risk nursing home (NH) residents is cost-effective and has a positive effect on residents' between-meal intake.…”
Section: Nursing Ee On Nurse Education and Managementmentioning
confidence: 99%
“…If you don’t know how, read Opperman et al’s (2016) article that teaches how to calculate ROI. Then, read Garrison and Beverage’s (2018) Journal for Nurses in Professional Development article to learn how they made measuring ROI an expectation in their department.…”
mentioning
confidence: 99%